Embodied energy and CO2 emissions of life cycle assessment (LCA) in the traditional and contemporary Iranian construction systems. (July 2021) - Pakdel, Ali; Ayatollahi, Hossein; Sattary, Sattar
Abstract: The Iranian building sector is the second contributor in energy consumption and carbon emissions. While the conventional construction systems and industrial building material in this industry are exacerbating the situation, the use of traditional techniques and earthen sustainable materials are left out. This paper seeks to unravel the environmental benefits of using traditional techniques, and earthen materials in the context of Yazd city. To do this, embodied and the operational energy and carbon emissions are selected to be investigated. Using LCA methodology, embodied and operational energy and carbon emissions of a pilot passive building which is built by Traditional Techniques and Materials (TTM) is compared with a building constructed by conventional systems and materials (CSM). Based on the results, the embodied energy and carbon emissions of TTM is 2.86 GJ/m 2 and 220 kg CO2 eq/m 2 which shows 43% and 48% decrease compared to CSM, respectively. Also the operational energy and carbon emissions are 0.35 GJ/m 2 and 68.25 kg CO2 eq/m 2 which are 88% and 81% lower than those of CSM, respectively. The main conclusion of this study is that due to the short life span of buildings in Iran, the impact of embodied energy on the life cycle of both TTM and CSM is significant, Moreover, the embodied energy constitute a larger share in TTM overall life cycle energy (89.1%). By comparing TTM and CSM, it is also concluded that the traditional techniques and earthen materials could have a profound impact on the overall life cycle energy and carbon emissions. Highlights: The short buildings life span in Iran has a significant impact on the embodied energy of buildings. Iranian traditional techniques could have a positive impact on the overall life cycle energy and carbon emissions. The embodied energy of Green Guesthouse is in the common range of 16 earthen, passive buildings all over the world.